Regulation of dorso‐ventral polarity by the nerve cord during annelid regeneration: A review of experimental evidence - Boilly, Bénoni (Regeneration (Oxf), 2017)
An important goal for understanding regeneration is determining how polarity is conferred to the regenerate. Here we review findings in two groups of polychaete annelids that implicate the ventral nerve cord in assigning dorso‐ventral polarity, and specifically ventral identity, to the regenerate. In nereids, surgical manipulations indicate that parapodia develop where dorsal and ventral body wall territories contact. Without a nerve cord at the wound site, the regenerate differentiates no evident polarity (with no parapodia) and only dorsal identity, while with two nerve cords the regenerate develops a twinned dorso‐ventral axis (with four parapodia per segment instead of the normal two). In sabellids, a striking natural dorso‐ventral inversion in parapodial morphology occurs along the body axis and this inversion is morphologically correlated with the position of the nerve cord. Parapodial inversion also occurs in segments in which the nerve cord has been removed, even without any segment amputation. Together, these data strongly support a role for the nerve cord in annelid dorso‐ventral pattern regulation, with the nerve cord conferring ventral identity.